2023
DOI: 10.1096/fj.202301722r
|View full text |Cite
|
Sign up to set email alerts
|

Lactate produced by alveolar type II cells suppresses inflammatory alveolar macrophages in acute lung injury

René M. Roy,
Ayed Allawzi,
Nana Burns
et al.

Abstract: Alveolar inflammation is a hallmark of acute lung injury (ALI), and its clinical correlate is acute respiratory distress syndrome—and it is as a result of interactions between alveolar type II cells (ATII) and alveolar macrophages (AM). In the setting of acute injury, the microenvironment of the intra‐alveolar space is determined in part by metabolites and cytokines and is known to shape the AM phenotype. In response to ALI, increased glycolysis is observed in AT II cells, mediated by the transcription factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In this way, c-Maf mediates a trade-off in AMs between proliferative capacity and production of IL-10. While production of IL- 10 early during an infection response might be detrimental to mounting effective host immune responses 55,56 , IL-10 is critical during chronic disease and inflammation to prevent immunopathology, including under conditions such as Acute Lung Injury (ALI) 57 . Further investigation is needed into the potential in vivo and context-dependent impacts of AM IL-10 production.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, c-Maf mediates a trade-off in AMs between proliferative capacity and production of IL-10. While production of IL- 10 early during an infection response might be detrimental to mounting effective host immune responses 55,56 , IL-10 is critical during chronic disease and inflammation to prevent immunopathology, including under conditions such as Acute Lung Injury (ALI) 57 . Further investigation is needed into the potential in vivo and context-dependent impacts of AM IL-10 production.…”
Section: Discussionmentioning
confidence: 99%
“…Functional cell death caused by sustained hyper-lactate environments may worsen local hypoxia, promote lactate production, and lead to a vicious cycle of tissue damage in sepsis [ 37 ]. However, some studies have suggested that lactate can inhibit the release of inflammatory cytokines in macrophages during acute lung injury, indicating heterogeneity in its effects on different cells [ 38 ]. Recent research has found lactate to be a more efficient carbon source than glucose in the tricarboxylic acid cycle [ 39 ].…”
Section: Discussionmentioning
confidence: 99%